Identification of a Protein Network Driving Neuritogenesis of MGE-Derived GABAergic Interneurons - Franchi, Sira A.; Astro, Veronica; Macco, Romina; Tonoli, Diletta; Barnier, Jean-Vianney; Botta, Martina; de Curtis, Ivan (Frontiers in Cellular Neuroscience, 2016)
Interneurons are essential modulators of brain activity and their abnormal maturation may lead to neural and intellectual disabilities. Here we show that cultures derived from murine medial ganglionic eminences (MGEs) produce virtually pure, polarized γ-aminobutyric acid (GABA)-ergic interneurons that can form morphologically identifiable inhibitory synapses. We show that Rac GTPases and a protein complex including the GIT family scaffold proteins are expressed during maturation in vitro, and are required for the normal development of neurites. GIT1 promotes neurite extension in a conformation-dependent manner, while affecting its interaction with specific partners reduces neurite branching. Proteins of the GIT network are concentrated at growth cones, and interaction mutants may affect growth cone behavior. Our findings identify the PIX/GIT1/liprin-α1/ERC1 network as critical for the regulation of interneuron neurite differentiation in vitro, and show that these cultures represent a valuable system to identify the molecular mechanisms driving the maturation of cortical/hippocampal interneurons.